Dampak Ketidakpastian Kebijakan Ekonomi Terhadap Persepsi Risiko Sektor Perbankan di Indonesia - Aulia, Putri; Satria, Doni (Universitas Negeri Padang, 2025)
This study aims to analyse the effect of Economic Policy Uncertainty (EPU) on banking risk perception in Indonesia. The data used is panel data from 48 commercial banks during the period 2007 to 2023. The analysis method used is panel data regression with Seemingly Unrelated Regression (SUR) approach and processed using EViews software. The results showed that the variables of EPU, Gross Domestic Product (GDP), inflation, Return on Assets (ROA), and Loan to Deposit Ratio (LDR) had a significant effect on the perception of banking risk. An increase in EPU has an effect on increasing risk perception, which indicates that banks tend to be more cautious in the face of economic policy uncertainty. In addition, macroeconomic variables such as inflation, GDP, ROA, and LDR also influence changes in bank risk perception. This finding confirms the important role of macroeconomic factors in managing risk and maintaining the stability of the banking sector in Indonesia.